The Role of Physical Activity and Physical Exercise in Improving Health (Literature Review Sport Education) - Siska Aprelyani (Siber International Journal of Sport Education, 2024)
Literature Review The Role of Physical Activity and Physical Exercise in Improving Health is a scientific article with the aim of analyzing whether Physical Activity and Physical Exercise in improving health. The method examines various studies, articles, and books that are relevant to the topic discussed. The results of this article are: 1) Physical Activity plays a role in Improving Health 2) Physical Exercise plays a role in Improving Health. Apart from these 2 exogenous variables that affect the endogenous variable of Leader Character, there are still many other factors including the environment, service, behavior.